ELISA-based serological survey of Mycoplasma bovis in cattle in three local government areas in Adamawa State, Nigeria - Francis, Markus Isa; Raji, Mashood Abiola; Kazeem, Haruna Makanjuola; Suleiman, Mohammed Musa (Journal of Advanced Veterinary and Animal Research, 2015)
A serological survey for the detection of antibodies to Mycoplasma bovis was conducted in Adamawa State, Nigeria during the year 2012. A total of 400 serum samples were collected from three local government areas (LGA) namely Yola (n=140), Mubi (n=130) and Ganye (n=130), and the samples were examined for the presence of M. bovis antibodies using BIO-X M. bovis antibody ELISA Kit. The overall seroprevalence of M. bovis was recorded as 19.5% (n=78/400). The highest seroprevalence was recorded in Ganye LGA (27.7%; n=36/130), followed by Yola LGA (20.0%; n=28/140) and Mubi LGA (10.8%; n=14/130). The cattle aging <1-year had the highest prevalence (25.8%), followed by 4-year-old cattle (22.4%). Based on sex distribution, 20.4% of the cows and 17.4% of the bulls were seropositive to M. bovis. Breed susceptibility to M. bovis infection showed that White Fulani had the highest prevalence (21.8%), and Sokoto Gudali had the lowest (11.9%). No statistical significant association was found between M. bovis infection and age, sex and breed of the cattle. In conclusion, the above findings are indicative for the presence of M. bovis in the study area. http://dx.doi.org/10.5455/javar.2015.b77